Impact of Dietary Protein Restriction on the Immunogenicity and Efficacy of Whole-Sporozoite Malaria Vaccination - Nunes-Cabaço, Helena; Moita, Diana; Rôla, Catarina; Mendes, António M.; Prudêncio, Miguel (Frontiers in Immunology, 2022)
Malaria remains one of the world’s most prevalent infectious diseases. Several vaccination strategies currently under investigation aim at hampering the development of the Plasmodium parasite during the clinically silent liver stage of its life cycle in the mammalian host, preventing the subsequent disease-associated blood stage of infection. Immunization with radiation-attenuated sporozoites (RAS), the liver-infecting parasite forms, can induce sterile protection against malaria. However, the efficacy of vaccine candidates in malaria-naïve individuals in high-income countries is frequently higher than that found in populations where malaria is endemic. Malnutrition has been associated with immune dysfunction and with a delay or impairment of the immune response to some vaccines. Since vaccine efficacy depends on the generation of competent immune responses, and malaria-endemic regions are often associated with malnutrition, we hypothesized that an inadequate host nutritional status, specifically resulting from a reduction in dietary protein, could impact on the establishment of an efficient anti-malarial immune response. We developed a model of RAS immunization under low protein diet to investigate the impact of a reduced host protein intake on the immunogenicity and protective efficacy of this vaccine. Our analysis of the circulating and tissue-associated immune compartments revealed that a reduction in dietary protein intake during immunization resulted in a decrease in the frequency of circulating CD4+ T cells and of hepatic NK cells. Nevertheless, the profile of CD8+ T cells in the blood, liver and spleen was robust and minimally affected by the dietary protein content during RAS immunization, as assessed by supervised and in-depth unsupervised X-shift clustering analysis. Although mice immunized under low protein diet presented higher parasite liver load upon challenge than those immunized under adequate protein intake, the two groups displayed similar levels of protection from disease. Overall, our data indicate that dietary protein reduction may have minimal impact on the immunogenicity and efficacy of RAS-based malaria vaccination. Importantly, this experimental model can be extended to assess the impact of other nutrient imbalances and immunization strategies, towards the refinement of future translational interventions that improve vaccine efficacy in malnourished individuals.